Developmental regulation of oocyte lipid intake through 'patent' follicular epithelium in Drosophila melanogaster. - Row, S.; Huang, Y.C.; Deng, W.M. (iScience, 2021)
Epithelia form protective permeability barriers that selectively allow the exchange of material while maintaining tissue integrity under extreme mechanical, chemical, and bacterial loads. Here, we report in the Drosophila follicular epithelium a developmentally regulated and evolutionarily conserved process "patency", wherein a breach is created in the epithelium at tricellular contacts during mid-vitellogenesis. In Drosophila, patency exhibits a strict temporal range potentially delimited by the transcription factor Tramtrack69 and a spatial pattern influenced by the dorsal-anterior signals of the follicular epithelium. Crucial for growth and lipid uptake by the oocyte, patency is also exploited by endosymbionts such as Spiroplasma pulsonii. Our findings reveal an evolutionarily conserved and developmentally regulated non-typical epithelial function in a classic model system.